Parent-child dyads and nuclear family association in pedometer-assessed physical activity: A cross-sectional study of 4-to-16-year-old Czech children - Sigmundová, Dagmar; Badura, Petr; Sigmund, Erik (European journal of sport science, 2021)
The main aim of this study is to examine familial aggregation in pedometer-assessed physical activity (PA) and proxy-reported screen time (ST) with estimating which of the parents' lifestyle indicators help their offspring achieve step count (SC) recommendations under daily life conditions. The analysis included 773 parent-child dyads (591 mother-child, 182 father-child) and 511 nuclear family triads (mother-father-child) with data ambulatory PA monitored with a Yamax pedometer during a regular school/working week during the spring and autumn between 2013 and 2019. Based on Logistic regression analysis, an achievement of 10,000 steps a day by the mothers significantly (p < 0.001) increases the odds ratio of their children reaching the recommended daily SC in the parent-child dyads. Obesity/overweight of mothers (fathers) significantly (p < 0.05) increases (reduces) the chance of their children reaching the recommended daily SC in the analysis of the nuclear family triads. For both overweight/obese and non-overweight children, the odds of reaching the recommended daily SC are significantly (p < 0.05) increased by their regular participation (≥ twice per week) in organised leisure-time PA (analysis of the nuclear family triads) and non-excessive entertainment ST (≤2 h per day) in the mother-child and nuclear family triads. Despite the different mother-/father-child behavioural associations, SC of parents are positively associated with SC of their children (Linear regression analysis). The involvement of children in regular participation in organised leisure activities (at least twice a week) and limiting their excessive entertainment ST might be important factors contributing to the achievement of the recommended daily SC by children.
Keywords: Cross-Sectional Studies; entertainment screen time; Leisure Activities; Male; Overweight; Child, Preschool; Obesity; fitness náramky; Adolescent; Česká republika; Child; Screen Time; dítě; obezita; Adult; dospělí; Life Style; mužské pohlaví; nadváha; step counts; Exercise; mladiství; Czech Republic; předškolní dítě; Family Relations; parent–child dyads; životní styl; lidé; Physical activity; ženské pohlaví; volnočasové aktivity; Humans; nuclear family triads; čas strávený před obrazovkou; rodinné vztahy; průřezové studie; Fitness Trackers; Female; cvičení; lidé středního věku; Middle Aged